Effect of an electrolyte flow on electrochemical hydrogen permeation (2014)
The influence of an electrolyte flux injection over the detection side on pure iron membranes on electrochemical hydrogen permeation test was studied. A modified Devanathan´s cell was used in the experiments. This cell allows the injection of an electrolyte flux over the hydrogen exit side during the permeation tests. In the hydrogen generation compartment a NaOH 0.1M + 2mgL-1 As2O3 solution was used applying a constant current of 2.85 mA. The detection side was maintained under potentiostatic control at potential values in the passivity range for iron. The solution used in the exit compartment was a borate buffer (pH=8.4). It was not observed a significant variation of the permeation current when an electrolyte flow was injected on iron samples, however, a slightly raise both of the steady state of permeation current density and the calculated permeation parameters was observed in the tests in which an electrolyte flux was applied.